2010
DOI: 10.1007/s11250-010-9652-9
|View full text |Cite
|
Sign up to set email alerts
|

Supporting small-scale dairy farmers in increasing milk production: evidence from Morocco

Abstract: This study aimed to evaluate the effects of technical support provided to five small-scale cattle farms in the Tadla irrigation scheme (Morocco) on their milk yield. The first stage consisted of assessing the initial management of dairy herds, especially feeding strategies, and their effects on milk output. This diagnosis revealed major gaps between the existing and the potential milk yield, due to insufficient and imbalanced dietary rations. Based on this diagnosis, technical support was adapted to the realit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Moreover, the nature of the available forages implied unbalanced dietary rations, thus resulting in nutrient wastage and reduced output of cattle products. Similar findings were published in previous studies in emerging countries (Moran, 2013;Sraïri et al, 2015), implying the need to generalize support to smallholder farms for cattle feed formulation to increase dairy production (Sraïri et al, 2011). The milk delivered per lactating cow only reached an average value of 1465 kg/year, whereas the potential is 3500 kg for crossbred Holstein × local cows.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the nature of the available forages implied unbalanced dietary rations, thus resulting in nutrient wastage and reduced output of cattle products. Similar findings were published in previous studies in emerging countries (Moran, 2013;Sraïri et al, 2015), implying the need to generalize support to smallholder farms for cattle feed formulation to increase dairy production (Sraïri et al, 2011). The milk delivered per lactating cow only reached an average value of 1465 kg/year, whereas the potential is 3500 kg for crossbred Holstein × local cows.…”
Section: Discussionsupporting
confidence: 86%
“…It was found that 16.7% farmers had training on dairy farms and 83.3% farms had no training on dairy farm management. This result is contraindicated with Sriri et al [13] but agree with Hossain et al [12] who reported that 18% farmers had training on dairy farms and 81% farms had no training on dairy farm management. For establishing dairy farms, 7% of dairy farmers were dependent on bank loan, 10% on their own sources and 83 % on bank loan and own source.…”
Section: General Information Of Small Dairy Farm Ownerssupporting
confidence: 58%
“…In this case, it may make the farmers do not count the production input costs spent for the business as well as revenue acquired. Srairi et al (2011) stated that milk production could be rapidly improved by balancing dietary rations that enabled the average milk yield of lactating cows to be reached, optimising feed costs and reducing the cost of milk production. If the production input cost and the revenue are counted and economically alocated, the dairy cattle business could be profitable.…”
Section: Introductionmentioning
confidence: 99%